2011
DOI: 10.1111/j.1365-2125.2011.04023.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on cytochrome P450 1A2 activity

Abstract: Cigarette smoking accelerates the metabolism of certain drugs, particularly those primarily metabolized by cytochrome P450 1A2 (CYP1A2) and, to a lesser extent, CYP2E1 and some UDP-glucuronosyltransferases [1,2]. The induction of CYP1A2 is mediated by binding of polycyclic aromatic hydrocarbons of the tobacco smoke to the aryl hydrocarbon receptor (AHR) with consequent transcriptional activation of the CYP1A2 gene. Furthermore, CYP1A1 and CYP1B1 enzymes are induced by tobacco smoking via AHR in various human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…Inhibition of CYP2A6‐mediated nicotine metabolism by constituents of coffee prolongs nicotine's clearance may be similar to the established impact of reduced nicotine metabolizer phenotype on reducing smoking in these smoking coffee consumers 20. It is known that smoking induces the enzyme cytochrome P450 1A2 (CYP1A2) (the main enzyme involved in caffeine metabolism), and therefore increases metabolism of caffeine 21, 22. It is also possible that constituents of coffee may have a pharmacological impact on the actions or metabolism of nicotine 1.…”
Section: Discussionmentioning
confidence: 89%
“…Inhibition of CYP2A6‐mediated nicotine metabolism by constituents of coffee prolongs nicotine's clearance may be similar to the established impact of reduced nicotine metabolizer phenotype on reducing smoking in these smoking coffee consumers 20. It is known that smoking induces the enzyme cytochrome P450 1A2 (CYP1A2) (the main enzyme involved in caffeine metabolism), and therefore increases metabolism of caffeine 21, 22. It is also possible that constituents of coffee may have a pharmacological impact on the actions or metabolism of nicotine 1.…”
Section: Discussionmentioning
confidence: 89%
“…12,14 CYP1A2 is the primary enzyme responsible for metabolizing caffeine, whilst AHR controls transcription of CYP1A2. 15 Combining variants in these regions into a multiple allelic genetic risk score increases the proportion of variance in caffeine consumption explained and hence increases power. 10 It is important to note that these variants are likely to affect consumption through their effects on caffeine metabolism (i.e., slow metabolism of caffeine results in reduced consumption), so these instruments may have opposing effects on blood caffeine levels; the allele in AHR which increases coffee consumption was associated with lower blood caffeine in a GWAS of blood metabolites.…”
Section: What's New?mentioning
confidence: 99%
“…Two key genetic loci are close to the cytochrome P450 1A1/2 ( CYP1A1/CYP1A2 ) and aryl hydrocarbon receptor ( AHR ) genes, which are known to play a functional role in caffeine metabolism . CYP1A2 is the primary enzyme responsible for metabolizing caffeine, whilst AHR controls transcription of CYP1A2 . Combining variants in these regions into a multiple allelic genetic risk score increases the proportion of variance in caffeine consumption explained and hence increases power .…”
mentioning
confidence: 99%
“…The one exception to this generalization was that exposure to nicotine for 3 d, but not 1 or 7 d, downregulated hippocampal CYP1A2 expression. Evidence for CY1A2 transcriptional regulation by nicotine in liver and/or brain has been shown in rodents (Anandatheerthavarada et al, 1993b; Price et al, 2004), although in humans, nicotine has been reported to have no effect on CYP1A2 activity (Hukkanen et al, 2011). CYP1A2 has been implicated in PCB metabolism (Fitzgerald et al, 2005; Zhou et al, 2010; Curran et al, 2011); however, whether its transient downregulation in the hippocampus is functionally relevant to PCB neurotoxicity has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%